Cervical Caries: Modern Methods of Diagnosis and Treatment - Alexei Yumashev (Journal of Global Pharma Technology, 2016)
Objective: The purpose of this study is to study the effectiveness of the cervical caries treatment when filling with different materials in the short and long term. Methods: To study the elemental composition, electron probe microanalysis method was used. The quality of fillings from NC, GC, CM was evaluated in the following terms: a week after restoration, six months, a year, two years. Results: Features of the anatomical structure of the cervical region indicate an increased risk of caries here. Areas with increased tissue hardness, as well as hardness, stability and mineralization may form in the dental tissue. These foci are able to withstand the demineralization of the tooth for some time. Conclusions: When filling NC and CM in the intermediate layer between dentin and material, the structure is homogeneous. The hard tissues of the tooth are enriched due to the contained fluorides. Scanning microscopy data confirmed the opening of the dentinal tubules. The first group of patients (low resistance to caries) improved 1.4 times the performance of the marginal fit of the fillings, provided that ozonation was present (p≤0.05). For the second group, the safety of fillings was established for 2 years in 95% of cases, but subject to the presence of ozonation.Keywords: Cervical caries, Ozonation, Nanocomposites, Glass ion cements, Nanoglassionomer, compomer.